2015
DOI: 10.1017/cem.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Educational and Mentorship Program for Emergency Medicine Women Residents to Enhance Academic Development and Retention

Abstract: Given the discrepancy between men and women's equal rates of medical school matriculation and their rates of academic promotion and leadership role acquisition, the need to provide mentorship and education to women in academic medicine is becoming increasingly recognized. Numerous large-scale programs have been developed to provide support and resources for women's enrichment and retention in academic medicine. Analyses of contributory factors to the aforementioned discrepancy commonly cite insufficient mentor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Specific strategies to combat female resident burnout include dedicated mentorship and sponsorship programs with female faculty who could serve as potential role models for young trainees . Female residents should be included in conversations about wellness and combating burnout during residency.…”
Section: Strategies Across the Career Continuum: Priming The Pipelinementioning
confidence: 99%
“…Specific strategies to combat female resident burnout include dedicated mentorship and sponsorship programs with female faculty who could serve as potential role models for young trainees . Female residents should be included in conversations about wellness and combating burnout during residency.…”
Section: Strategies Across the Career Continuum: Priming The Pipelinementioning
confidence: 99%
“…The impact of the existing gender gap on the organizational effectiveness and workplace culture of academic medical centers has yet to be explored. Furthermore, there is scant evidence that supports interventions to counter the gender gap in academic medicine [ 26 28 ]. Academic physicians may have suggestions regarding potential strategies to bridge this gap based on their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The aspect of mentorship in education research is essential, and other health sciences mentorship research illustrates its importance. Previous research with nurses (Nowell et al, 2017), emergency medicine residents (Bhatia et al, 2015;Perry et al, 2015), and medical faculty (Pololi et al, 2015;Mylona et al, 2016) has described the importance of mentorship programs for these populations, as these programs provide an ongoing support structure for junior learners that may extend well past the duration of the program. In fact, Pololi et al (2015) and Mylona et al (2016) found in their surveys of academic health centers that when mentoring is inadequate, faculty are more likely to express dissatisfaction with and potentially leave their institution.…”
Section: Introductionmentioning
confidence: 99%